Investigating clonal hematopoiesis in rhesus macaque and human - Zhou, Yifan (Apollo - University of Cambridge Repository, 2024)
Introduction
Clonal hematopoiesis (CH) describes the expansion of blood cell output from one HSPC linked to an acquired somatic mutation conferring a competitive advantage. While clonality is a feature of hematological malignancies, recent large deep sequencing studies have revealed that clonally-expanded HSPC with specific somatic mutations are also prevalent in individuals without overt hematological abnormalities and become increasingly common with age. The phenomenon is thus termed age-related clonal hematopoiesis (ARCH). Individuals with CH are at greater risk for hematologic malignancies and cardiovascular diseases. However, predictive long-term preclinical animal models to recapitulate the spectrum of human CH are lacking. Such models would provide the opportunity to study parameters impacting the CH expansion and therapeutic options. CH expansions Furthermore, though CH has been shown to lead to hyperinflammation in murine models, its clinical implication in inflammatory disease such as COVID-19 has yet to be understood. Objectives 1. To examine the CH mutation landscape in blood cells from aged rhesus macaques (RMs) and to develop an autologous transplantation model of CH in RM to examine the impact of CH and potential therapeutic strategies long term. 2. To assess the impact of CH on COVID-19 disease severity in CH RM model and in human patients. 3. To study the competitive fitness of *RUNX1* mutant hematopoietic stem cells (HSPCs) in RM autologous transplant model. Results
Through error-corrected sequencing of 56 human CH/myeloid malignancy genes, we identified natural CH driver mutations in aged RMs matching genes somatically mutated in human CH, with *DNMT3A* and *TET2* mutations being the most frequent. Of the 60 aged RM (median age of 25 years), 12 (20%) were to carry naturally occurring driver CH mutations and showed a trend of increasing with age. On the other hand, in the autologous transplantation RM model of CH, heterozygous *TET2* loss-of-function mutations led to reproducible and significant expansion of multiple HSPC clones. Although the blood counts of these CH macaques were normal, their bone marrows were hypercellular and myeloid-predominant. *TET2*-disrupted myeloid colony-forming units isolated from these animals showed a distinct hyperinflammatory gene expression profile compared to WT. In addition, mature macrophages purified from the CH macaques showed elevated NLRP3 inflammasome activity and increased interleukin (IL)-1 and IL-6 production. The model was used to test the impact of IL-6 blockage by tocilizumab, documenting a slowing of *TET2* mutated expansion, suggesting that interruption of the IL-6 axis may remove the selective advantage of mutant HSPCs. These findings provide a model for examining the pathophysiology of CH and give insights into potential therapeutic interventions. We next subjected our CH RM model to SARS-CoV2 infection given the overlapping role of inflammation in COVID-19 disease pathophysiology. However, we did not find evidence supporting CH worsening COVID-19 disease pathophysiology. This was confirmed by screening CH mutation in COVID-19 patient (N = 568) cohort of different severity. We concluded that CH was associated with Covid-19 disease severity. Lastly in the autologous *RUNX1* mutant RM model, heterozygous *RUNX1* mutant HSPCs clonally cells expanded over time compared with control *AAVS1*-edited cells post autologous-transplant, potentially hindering corrective gene therapy for familial platelet disorder with associated myeloid malignancies patients with germline *RUNX1* mutation. Conclusions.
RM is a faithful model of human CH with naturally occurring aging associated CH mutations and engineered CH RM model recapitulates the phenotypes of human CH and allows for therapy testing. RM CH model offers a platform to assess clonal dynamics long term in different clinical setting, such as post autologous-transplant and gene therapy. RM CH model also provides important insights to the association between CH and COVID-19 disease, confirmed in patients study.
Keywords: aging; clonal hematopoiesis; human; informatics; mutation; NGS; rhesus macaque